Studies on Raspy Crickets: Astyloplatum n. gen. a new gryllacrid genus from Colombian Andes (Orthoptera: Gryllacrididae) - Cadena-Castañeda, Oscar J.; M., Didier Castañeda; Garay, Andrea; García, Alexander García (Zootaxa, 2023)
Astyloplatum luteolum n. gen. et n. sp., is described, as a new monospecific genus from the eastern slope of the Colombian Andes, of the middle and highlands of the departments of Boyacá and Santander. This new taxon is distinguished by its yellowish coloration and the lack of articulated stylli on the male subgenital plate; this character converges with several taxa unrelated to the tribe Gryllacridini in which Astyloplatum n. gen. is placed. The convergence of characters in gryllacridines, diversity, complement of the current classification, and the importance of the phallic complex for the delimitation of genera and species are discussed.